Serving End-Users in Sci-Tech Libraries, 1st edition - Mount, Ellis (Routledge, 2020)
This book, first published in 1984, analyses the various ways in which sci-tech libraries are meeting the needs of end-users in an era of fast-growing technical literature and increasingly complex tools and products used for the retrieval of information.